Effectiveness of 10% NaOH Fixation with Variations in Heating Temperature on The Quality of Preserved Preparations Pediculus humanus capitis - Acivrida Mega Charisma; Shinta Febriana Rochman (Universitas Airlangga, 2026)
Preserved preparations are sample preparations that are useful for looking at the morphology of ectoparasites, one of which is head lice (Pediculus humanus capitis). Making preserved preparations was carried out in 4 stages, starting with soaking the sample using 10% NaOH, dehydration, clearing, and mounting. Soaking the sample using 10% NaOH functions to soften the chitin layer on the exoskeleton which is the thick covering on the body surface of Pediculus humanus capitis. Therefore, in this research, optimization of temperature variations of the 10% NaOH immersion solution was carried out with temperature variations of 70°C, 75°C, 80°C, and 85°C to see the effectiveness of preparation formation. Each temperature variation was repeated 6 times so that 24 preparations were observed. In the research conducted, the most effective results were 70°C. The results of the research were then carried out statistical tests using the Kruskal Walis Test which obtained a figure of 0.004 > 0.005, which means that there was an influence of variations in heating temperature and 10% NaOH soaking on the quality of the Pediculus humanus capitis preparation.